English in Singapore - LISA LIM, ANNE PAKIR, and LIONEL WEE (Hong Kong University Press, 2010)
Of all Asian societies, the role of English in Singapore — at least from an outsider’s perspective — has typically been regarded as most successful and least contentious, compared to other English-using societies in the region. In contrast to Hong Kong, for example, the societal space for English as an interethnic lingua franca has meant that the rationale for English has often foregrounded its utility as a ‘neutral’ language of education and social administration. Singapore has also gained a strong reputation regionally for the relatively high proficiency of its English users, a reputation that has risen in pace with the city-state’s recent branding of itself as a knowledgebased community and arts and education hub. Ironically, however, at the same time that Singapore has worked hard to such ends, its domestic linguistic complaint tradition has striven less to emphasize its strengths, and somewhat more to bemoan the community’s collective mastery of English. While linguists have been fascinated by the emergence of local varieties of English, both educated and informal, the government has expressed much concern about the existence of ‘bad English’, which has often been equated with ‘Singlish’, however vaguely defined and described. Meanwhile, English continues to spread as a language of the home in a society where ‘mother tongue’ — for a number of official purposes — may only refer to such heritage languages as Mandarin, Malay, and Tamil.This present volume, edited by Lisa Lim, Anne Pakir, and Lionel Wee, is ground-breaking in the way in which it is able to account for and explain at least some of these contradictions and tensions. By engaging an ensemble of truly expert commentators on English in Singapore, this book succeeds in providing an insightful account of the interplay of linguistic ecology, language policies, and sociolinguistic realities of the Singapore community, which cumulatively offers a rich and fine-grained account of the sociolinguistics of English in this context. Part I (with a chapter from Lim, Pakir and Wee, and another from Lim) deals with the ecology of English in Singapore, where an integrated ‘ecological model’ requires an understanding of the dynamics of both migration and official language policies. Part II, with contributions from Gupta, Bruthiaux, and Alsagoff, then highlights the need to (re)conceptualize ‘English’ in the Singapore context, with particular reference to both the Speak Good English Movement, and the thorny issue of Singlish.